2013
DOI: 10.4161/hv.26136
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable particles as vaccine antigen delivery systems for stimulating cellular immune responses

Abstract: There is a need for both new and improved vaccination formulations for a range of diseases for which current vaccines are either inadequate or non-existent. Biodegradable polymer-based vaccines fulfill many of the desired properties in achieving effective long-term protection in a manner that is safe, economical, and potentially more practicable on a global scale. Here we discuss some of the work performed with micro/nanoparticles made from either synthetic (poly[lactic-co-glycolic acid] [PLGA] and polyanhydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…For more than two decades, the induction of CTLs by biodegradable PLGA microparticles has been investigated (17,21,(34)(35)(36)(37). However, despite the fact that the particles are easily recognized by APCs (38,39), that PLGA itself is immunologically inert (i.e., not recognized by specific Abs and eliminated by phagocytes), and that the particles can contain a high load of Ag that would facilitate CTLs and Th1-like immune responses, PLGA microparticles have not lived up to the initial expectations with regard to CD8 T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…For more than two decades, the induction of CTLs by biodegradable PLGA microparticles has been investigated (17,21,(34)(35)(36)(37). However, despite the fact that the particles are easily recognized by APCs (38,39), that PLGA itself is immunologically inert (i.e., not recognized by specific Abs and eliminated by phagocytes), and that the particles can contain a high load of Ag that would facilitate CTLs and Th1-like immune responses, PLGA microparticles have not lived up to the initial expectations with regard to CD8 T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(d,l-lactide-co-glycolide) (PLGA)-NPs, which are particularly attractive for clinical and biological applications because of their low toxicity, low immunogenicity, biocompatibility, and biodegradability, 12,13 have been widely utilized as drug carriers in nanomedicine. 14,15 These studies motivated us to know whether PLGA-NPs can increase the uptake efficiency of adjuvant or antigen by DCs and lead to an increase in antigen-specific CD8 + T cell responses.…”
Section: Introductionmentioning
confidence: 99%
“…PLGA-NPs are an attractive platform for payload delivery because of their biocompatibility, biodegradability, low toxicity, and low immunogenicity, which are key parameters for medical and pharmaceutical applications. 13 Moreover, payloads are frequently loaded within the particles, and their type and number may not affect the pharmacokinetics and biodistribution of the NPs. Recent work comparing adjuvant delivery has shown that the primary role is to increase DC maturation.…”
mentioning
confidence: 99%
“…Dendrimer nanoparticles with a uniform small size (about 90 nm) and many functional groups on the surface have been proposed as suitable carriers/adjuvants for presentation of subunit antigens [28]. The adjuvant effect of nanoparticles may include prolonged presentation, enhanced antigen uptake and direct stimulation of the innate immune system [29]. In this study, the G2 dendrimer nanoparticles were used as carriers and adjuvants and the immunogenicity of the conjugated protein was assessed in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%